Оцінювання метрологічних характеристик стандартних зразків EU-152, CS-137 І TH-232 з метою захисту населення від опромінення - Пустовий, А. С.; Озерський, К. Л. (ХНУРЕ, 2024)
The aim of this paper is to substantiate the approach to the assessment and evaluation of the uncertainty of the reference materials of europium-152 (Eu-152), cesium-137 (Cs-137) and thorium-232 (Th-232) during its production and calibration in accordance with the requirements of international regulatory documents. The uncertainty evaluation of the measurement result of a radioactive reference material with a natural half-life period is correct and reliable, taking into account its homogeneity and stability. Univariate analysis of variance is used as a tool for assessment stability, homogeneity and evaluating uncertainty.
Keywords: захист населення від опромінення; оцінювання метрологічних характеристик